The Adsorption and Regeneration of Natural Pumice as Low-Cost Adsorbent for Nitrate Removal From Water - Helard, Denny; Indah, Shinta; Sari, Chintia Maya; Mariesta, Hestia (UIR PRESS, 2018)
The potential of adsorption and regeneration of Indonesian natural pumice to remove nitrate from aqueous solution was studied in multiple adsorption-desorption cycles. Batch experiments were performed to examine the effect of various experimental parameters on the removal of nitrate. The optimum condition of nitrate removal by natural pumice were obtained at 3 of pH solution, 0.3 g/L of adsorbent dose, 30 min of contact time, <63 μm of particle size, and 90 mg/L of nitrate concentration with 54.79% of removal efficiency and 164.37 mg/g of nitrate uptake. The experimental data obtained were fitted with the Freundlich adsorption isotherm within the concentration range studied. Although complete desorption were not achieved, the result confirmed that HCl can be used as desorbing and recovery agent, which be desorbed 10-13% of nitrate ion. The used natural pumice also could be regenerated and reused up to three successive adsorption-desorption cycles. Overall results revealed that the ability of natural pumice to adsorb nitrate will create more interest to develop a new adsorbent from local mineral for pollutant removal from water